Diversity and composition of cactus species along an altitudinal gradient in the Sierras del Norte Mountains (Córdoba, Argentina) - Gurvich, Diego Ezequiel (2014)
Cacti are important elements of the flora in many ecosystems of the Americas. However, the factors that determine their richness and composition are not well known, particularly at the regional scale. The aim of this work was to study the patterns of cactus richness (both species and growth forms) and composition in the Sierras del Norte mountain range (Córdoba Province, Argentina). Species presence was recorded at 55 sites covering an altitudinal gradient from 203 to 970 m. Twenty four species from eight genera were recorded in the area. Total species richness and growth form richness decreased with increasing altitude. The richness of columnar and short columnar species decreased with increasing altitude, whereas richness of globose species increased. Opuntioid richness did not respond to altitude. Species composition was strongly related to altitude. Gymnocalycium bruchii and Parodia erinacea occurred at sites located at higher altitudes, whereas at sites at lower altitudes, Gymnocalycium schickendantzii, Stetsonia coryne and Cleistocactus baumannii, among other species, were present. Our results highlight the importance of altitude in shaping the distribution of species and growth forms in the Sierras del Norte Mountains.